2012
DOI: 10.1590/s1808-86942012000400017
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de alterações das células ciliadas externas em estudantes de uma escola do Distrito Federal

Abstract: Exposure to loud music is increasing among young people, and so could be the number of hearing impairment cases in this population. Otoacoustic emission tests are sensitive in capturing the effects of exposure to noise, and allow the detection of early cochlear disorders.Objective: This study aims to look into the prevalence rates of injuries to outer hair cells in a population of students through otoacoustic emission testing. Materials and Method:One-hundred and thirty-four subjects were submitted to transien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
0
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 17 publications
(21 reference statements)
1
0
0
Order By: Relevance
“…Therefore, the ears differed in amplitude in the research both with and without noise (Table 1); greater amplitude was observed in the right ear in both conditions. These findings confirmed data from the literature, which described greater TEOAE amplitudes in the right ear, as well as in female individuals 19,20 . Hence, even with the neurological injury, the individuals of the SG had results similar to those observed in people without this alteration.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, the ears differed in amplitude in the research both with and without noise (Table 1); greater amplitude was observed in the right ear in both conditions. These findings confirmed data from the literature, which described greater TEOAE amplitudes in the right ear, as well as in female individuals 19,20 . Hence, even with the neurological injury, the individuals of the SG had results similar to those observed in people without this alteration.…”
Section: Discussionsupporting
confidence: 91%
“…Previous research 6 found that most of the sample (94%) used earphones, and a considerable number of them (79%) had abnormal results in the examinations that assessed cochlear cell functioning. However, the authors deemed it necessary to conduct a study in further detail to investigate these young people's hearing habits concerning the frequency and time of device use and attendance at places with amplified music.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies approaching other types of hearing habits among young people pointed out that listening to music in earphones is the most frequent one 1,[4][5][6][7][8]11 . These data corroborate the findings in the present study and possibly reflect the lack of awareness among young people of the problem posed by this type of noise and its effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations